(untitled) (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
Plant secondary metabolites are applied in different areas, from the pharmaceutical, with the production of medicines, to agroindustrial, with their use as bioinsecticides. Vegetal species adapted to extreme environmental conditions, (low humidity and high temperatures), present a large diversity of secondary metabolites, being the Caatinga biome an example of extremist climates. The aim of this work was to evaluate the effect of crude extracts and enriched fractions of Manilkara rufula, a plant from the Caatinga, using the nervous system of cockroaches as a biological model. For this, adult Nauphoeta cinerea cockroaches of both sex, were used. The crude extract of M. rufula (CEMR) was administered at 25, 50 and 100 µg/g of animal and the methanolic (MFMR) and aqueous (AFMR) fractions were administrated at 10, 20 and 40 µg/g of animal. Also tested a octopamine neuromodulator (15 µg/g of animal) and phentolamine (0,01 µg/g of animal), an octopaminergic receptor antagonist. The neurolocomotor activity of the insects were tested, where the animals were monitored for 10 minutes with a webcam, and the records were analyzed by the software IDtracker® and Matlab ®. Behavioral grooming tests were performed, according to Sturmer et al. (2014). The neuromuscular activity was evaluated using the in vivo cockroach neuromuscular preparation (CNP), as described elsewhere (Martinelli et al. 2014). In neurolocomotion preparations, the CEMR (100 μg/g of animal) led to a considerable decrease of the traveled route by the animals, consequently increasing, the number of episodes in which the animals remained immobile. Our data suggest that the extracts of M. rufula may be acting on octopamine, associated with rhythmic behaviors such as locomotion and cleaning. In behavioral tests of grooming the CEMR (50 μg/g of animal) decreasing the leg cleaning behavior (controlled by the octopaminergic pathway) from 59±8 s/min (control) to 5±4 s/min (n=30). When octopamine was tested, the leg cleaning behavior was increased by 158±19 s/30 min. In contrast, phentolamine caused a decrease in leg grooming around 17±3 s/min. When CEMR (50 μg/g of animal) was administered minutes after administration of octopamine, there was a decrease in leg grooming around 62±10 s/30 min. In CNP assays, all CEMR concentrations decreased contraction force of insects. The CEMR (50 μg/g of animal) decreased contraction to 68±4% compared to control (101±1%; p 0,05). The neuromuscular junction is modulated mainly by Gamma-aminobutyric acid (GABA) and glutamate (GLU). The data suggest that extracts and fractions of M. rufula modulate the octopaminergic pathway, which in turn controls the release of GABA and GLU as an association neurotransmitter. The data obtained in this work demonstrate that the extracts of M. rufula have effect on the octopaminergic pathway of cockroaches, being the AFMR the main responsible for the observed effects, demonstrating the biotechnological potential of this species.